MEDIS (Mindfulness Meditation Combined with Tibetan Singing Bowls) for Dysmenorrhoea Among Adolescents: A Pre-experimental Study - I Gusti Agung Manik Karuniadi; Luh Putu Widiastini; Gusti Gede Mayun Surya Darma (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Dysmenorrhoea is one of the most prevalent menstrual disorders among adolescents. Non-pharmacological approaches, including mindfulness meditation and sound-healing therapies, are increasingly being explored as complementary pain-management strategies. Tibetan singing bowl therapy may promote relaxation through sound vibration and meditative effects, potentially reducing tension, anxiety, and pain. Combining these modalities may provide complementary psychophysiological benefits. This study examined changes in dysmenorrhoea pain scores before and after mindfulness meditation combined with Tibetan singing bowls among adolescents at SMPN 3 Abiansemal. Methods: This pre-experimental study used a one-group pre-test-post-test design. Forty adolescent girls aged 10-14 years who experienced dysmenorrhoea were recruited by purposive sampling. The intervention was delivered three times per week for two weeks before menstruation, with each session lasting 15 minutes. Pain intensity was measured using the Numeric Rating Scale (NRS). Data were analysed using the Wilcoxon signed-rank test. Results: Before the intervention, most participants experienced mild pain (67.5%), and the mean pain score was 2.57 ± 1.83. After the intervention, 57.5% of participants experienced mild pain and 37.5% reported no pain; the mean pain score was 1.17 ± 1.31. The Wilcoxon signed-rank test indicated a statistically significant reduction in dysmenorrhoea pain scores (Z = -4.916, p < 0.001). Conclusion: MEDIS was associated with a statistically significant reduction in dysmenorrhoea pain scores. Pending confirmation in more rigorous studies, the intervention may offer an accessible complementary approach to dysmenorrhoea pain management in adolescents.